Sliding mode control techniques for combined energy and attitude control system - Khouzani, Samira Eshghi (2015)
Attitude control and power storage subsystems are two of the essential utilities provided on a satellite. As they compromise a significant fraction of a satellite’s weight, a synergism concept that integrates these two into one subsystem can reduce the mass and volume of a satellite. The reduction will decrease the total cost of development and deployment of a satellite. A combined energy and attitude control system (CEACS) is an optimization concept that utilizes flywheels as a means of power storage and simultaneously as attitude actuators. A series of work on CEACS have proposed solutions for the satellite’s attitude control problems. However, the analysis disregarded the high non-linearity involved in the satellite’s attitude control itself. In addition, the proposed controllers’ feasibility in presence of unknown disturbances and uncertainties were not examined. This thesis addresses a more complex attitude-tracking problem. This work proposes the use of the sliding mode control technique for the attitude-tracking problem of CEACS. Furthermore, an enhanced sliding mode control (SMC) technique is introduced to achieve robustness against uncertainties and external disturbances. Integral Augmented Sliding Mode Control with Boundary Layer (ISMC-BL), a locally asymptotically stable controller, is developed to provide a robust and accurate solution for the CEACS’s attitude-tracking problem. The controller alleviates the chattering phenomenon influence on the attitude tracking performance that is associated with the conventional sliding mode using a boundary layer technique. Simultaneously, it reduces the steady-state error using an integral action. The numerical evaluation of the proposed controller demonstrates an enhanced attitude control accuracy in the presence of the system’s uncertainties and external disturbances. However, ISMC-BL suffers from overshoots in its transient response. In addition, the model focuses only on mission with small attitude orientations involved. Therefore, this thesis proposes a Nonsingular Terminal Sliding Mode (NTSM) control scheme for a global attitude-tracking mission of a CEACS. The nonlinear system herein is subjected to unknown but bounded disturbances and uncertainties. The Lyapunov stability theorem is used to prove the finite-time convergence in both reaching and sliding phase. The proposed method avoids the inherited singularity of conventional terminal sliding mode. The numerical analysis provides proofs of the controller’s robustness in rejecting the unknown disturbances and keeping the attitude errors as small as possible under the influence of uncertainties. The results provided by NTSM control method demonstrate the superiority of this sliding mode scheme compared to the previous proposed techniques for the CEACS’s attitude control.